Os crimes sexuais na província do Espírito Santo (1855-1889) - Mergar, Arion (2020)
The research refers to sexual crimes occurred in the County of Vitória, Province of Espírito Santo, from 1855 to 1889. By analyzing the speech of the defendants, the victims the witnesses and the State judicial system, the work aims at verifying the ideal